Implementation Of Palembang City Government Programs In Digital Marketing Transformation And Halal Certification - Putri, Intan; Syukerti, Nanda; Mulyadi, Ahmad Iman; Dendi, Dendi (KOMUNIKA, 2024)
The increasing number of MSMEs in Indonesia has become increasingly significant, especially amid developments in communication technology and during the COVID-19 pandemic in recent years. This research aims to determine the implementation of the Palembang City government program in supporting the digital transformation of MSMEs through digital marketing strategies. This qualitative descriptive study uses data collection techniques with in-depth interviews with the Department of Cooperatives and MSMEs in Palembang and MSME actors in Sekanak Lambidaro 26 Ilir, and will carry out observations and documentation. Determination of informants in this research was carried out using purposive sampling. Informants were selected deliberately based on criteria determined by the research objectives. The results of this research include culinary MSME players who have undergone a digital transformation, specifically in terms of digital payments and digital cashiers, as well as digital marketing, including creating logos, utilizing Google Maps, and employing sales applications such as marketplaces. E-commerce utilizes social media as a promotional medium, featuring various content, including social media marketing and online registration of halal certificates. The implementation of the Palembang City government's digital transformation program has not been evenly distributed, as evidenced by observations made by 3 out of 5 MSME informants who were unaware of its existence. Program, but the perpetrators participated in events organized by the Palembang City government.